The assessed value of non-invasive arterial stiffness parameters in the hypertensive nephropathy - HUANG Min; XIE Wei; ZHAO Dan (Linchuang shenzangbing zazhi)
Objective To explore the assessed value of non-invasive tests including carotid intima-media thickness(IMT),ankle brachial index(ABI) and cardio-ankle vascular index(CAVI) in the hypertensive nephropathy.Methods Forty-six patients diagnosed as hypertensive nephropathy by renal biopsy were classified as hypertensive nephropathy group from 2010 to 2014 in our hospital.At the same time,we selected 50 hypertension patients and 50 healthy subjects randomly as hypertension group and healthy control group.MIT,ABI,CAVI,urinary albumin-creatinine-ratio(ACR),urinary beta 2 microglobulin(β2-MG) and estimated glomerular filtration rate(eGFR) in these three groups were analyzed.Results The MIT,CAVI,ACR,and urinary β2-MG in hypertensive nephropathy group were significantly higher than in hypertension group or control group(P<3.01).MIT,CAVI,ACR and urinary β 2-MG in hypertension group were significantly higher than those in control group(P<0.05).ABI and eGFR in hypertensive nephropathy group were significantly lower than in other groups(P<0.01).ABI in hypertension group was significantly lower than in control group(P<0.01).There was no significant difference in eGFR between hypertension group and control group(P>0.05).Conclusions With the progression of hypertension,the degree of atherosclerosis becomes worse.It was suggested that ABI is positively correlated with the decline of renal function,and MIT or CAVI negatively with the declined renal function Glomerular filtration rate is related to atherosclerosis.Not only can non-invasive arterial stiffness parameters be used to quantitatively assess the extent of atherosclerosis in hypertension,but they also can serve as reliable indicators of disease progression that are valuable in evaluating the outcomes after physical or pharmacological treatment.